2017
DOI: 10.7554/elife.27670
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory receptor neurons use gain control and complementary kinetics to encode intermittent odorant stimuli

Abstract: Insects find food and mates by navigating odorant plumes that can be highly intermittent, with intensities and durations that vary rapidly over orders of magnitude. Much is known about olfactory responses to pulses and steps, but it remains unclear how olfactory receptor neurons (ORNs) detect the intensity and timing of natural stimuli, where the absence of scale in the signal makes detection a formidable olfactory task. By stimulating Drosophila ORNs in vivo with naturalistic and Gaussian stimuli, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
182
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(192 citation statements)
references
References 110 publications
10
182
0
Order By: Relevance
“…Together, our results suggest that navigation within spatiotemporally complex odor plumes is shaped by the sequence of encounters with individual odor packets. Both electrophysiological and behavioral measurements indicate that Drosophilaalong with other insects, mammals, and crustaceans, among otherscan precisely encode odor timing within their signal transduction cascade [35,38,41,42]. Our findings suggest that Drosophila leverage this capability to navigate their olfactory world.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Together, our results suggest that navigation within spatiotemporally complex odor plumes is shaped by the sequence of encounters with individual odor packets. Both electrophysiological and behavioral measurements indicate that Drosophilaalong with other insects, mammals, and crustaceans, among otherscan precisely encode odor timing within their signal transduction cascade [35,38,41,42]. Our findings suggest that Drosophila leverage this capability to navigate their olfactory world.…”
Section: Introductionmentioning
confidence: 70%
“…Instead, flies execute stochastic, stereotyped 30-degree saccades at a rate independent of the duration or frequency of odor encounters. Upwind bias results not from modulating turn magnitude or frequency but rather turn direction: the randomly-occurring saccades are more likely to be oriented upwind when the frequency of odor encountersbut not their duration or concentrationis high, suggesting an important role for precise odor timing detection [35][36][37][38]. Prior studies have shown that flies increase walking speed at the onset of a uniform odor blocks [20,39,40].…”
Section: Introductionmentioning
confidence: 96%
“…Recently, Cao et al published a phenomenological model to characterize the peak and the steady response of sensory adaption for fruit fly OSNs (Cao et al, 2016). Gorur-Shandilya et al proposed a two-state model for the fruit fly odorant receptors that can reproduce Weber-Fechner's law observed in physiological recordings (Gorur-Shandilya et al, 2017). In addition, De Palo et al (De Palo et al, 2013) proposed an abstract/phenomenological model with feedback mechanism that characterizes the common dynamical features in both visual and olfactory sensory transduction.…”
Section: Modelmentioning
confidence: 99%
“…The responses of ORNs to diverse odorants of the same concentration differ widely, due to differences in odor-receptor affinities [6,31,32] and stimulus dynamics [33]. However, downstream from this input nonlinearity, signal transduction and adaptation dynamics exhibit a surprising degree of invariance with respect to odor-receptor identity: reverse-correlation analysis of ORN response to fluctuating stimuli produces highly stereotyped, concentration-invariant response filters [18,33,34].…”
mentioning
confidence: 99%
“…These properties stem in part from an apparently invariant adaptive scaling law in ORNs: gain varies inversely with mean odor concentration according to the Weber-Fechner Law of psychophysics [35,36], irrespective of the odor-receptor combination [34,37,38]. The invariance of this relatively fast adaptation (∼250 ms) can be traced back to feedback mechanisms in odor transduction, upstream of ORN firing [34,[37][38][39], which depend on the activity of the signaling pathway rather than on the identity of its receptor [39]. The generality of the adaptive scaling suggests it could be mediated by the highly conserved Orco co-receptor [40][41][42][43].…”
mentioning
confidence: 99%